Metabolomics and transcriptomics of pheromone biosynthesis in an aggressive forest pest Ips typographus - Ramakrishnan, Rajarajan; Hradecký, Jaromír; Roy, Amit; Kalinová, Blanka; Mendezes, Rya C; Synek, Jiri; Bláha, Jaromír; Svatoš, Aleš; Jirošová, Anna (Insect biochemistry and molecular biology, 2022)
Eurasian spruce bark beetle, Ips typographus, is a destructive pest in spruce forests. The ability of I. typographus to colonise host trees depends on its massive aggregation behaviour mediated by aggregation pheromones, consisting of 2-methyl-3-buten-2-ol and cis-verbenol. Other biologically active compounds such as ipsdienol and verbenone have also been detected in the beetle. Biosynthesis of 2-methyl-3-buten-2-ol and ipsdienol de novo from mevalonate and that of cis-verbenol from α-pinene sequestrated from the host have been reported in preliminary studies. However, knowledge on the molecular mechanisms underlying pheromone biosynthesis in this pest is currently limited. In this study, we performed metabolomic and differential gene expression (DGE) analysis for the pheromone-producing life stages of I. typographus. The highest amounts of 2-methyl-3-buten-2-ol (238 ng/gut) and cis-verbenol (23 ng/gut) were found in the fed male gut (colonisation stage) and the immature male gut (early stage), respectively. We also determined the amount of verbenyl oleate (the possible storage form of cis-verbenol), a monoterpenyl fatty acid ester, to be approximately 1604 ng/mg in the immature stage in the beetle body. DGE analysis revealed possible candidate genes involved in the biosynthesis of the quantified pheromones and related compounds. A novel hemiterpene-synthesising candidate isoprenyl-di-phosphate synthase Ityp09271 gene proposed for 2-methyl-3-buten-2-ol synthesis was found to be highly expressed only in the fed male beetle gut. Putative cytochrome P450 genes involved in cis/trans-verbenol synthesis and an esterase gene Ityp11977, which could regulate verbenyl oleate synthesis, were identified in the immature male gut. Our findings from the molecular analysis of pheromone-producing gene families are the first such results reported for I. typographus. With further characterisation of the identified genes, we can develop novel strategies to disrupt the aggregation behaviour of I. typographus and thereby prevent vegetation loss.
Keywords: systém (enzymů) cytochromů P-450; stravovací zvyklosti; Esterases; Picea; feromony; Weevils; Forests; Bark beetle; kontrola škůdců; Pest Control; nosatcovití; Metabolomics; lesy; Bicyclic Monoterpenes; de novo; metabolomika; zvířata; sekundární metabolismus; bicyklické monoterpeny; Genes, Insect; Pheromone biosynthesis; Cytochrome P-450 Enzyme System; Pheromones; stanovení celkové genové exprese; esterasy; transkriptom; hmyzí geny; Omics; Transcriptome; Animals; Gene Expression Profiling; smrk; Secondary Metabolism; Gut tissue; Feeding Behavior; Gastrointestinal Tract; Spruce; gastrointestinální trakt